FRI0179 A STUDY ON THE ACHIEVEMENT OF LUPUS LOW DISEASE ACTIVITY STATE AND QUALITY OF LIFE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: FROM THE JUNTENDO UNIVERSITY SLE PROSPECTIVE REGISTRY STUDY. (2nd June 2020) - Matsushita, M.; Amano, H.; Nozawa, K.; Ogasawara, M.; Tada, K.; Kempe, K.; Kusaoi, M.; Kawamoto, T.; Minowa, K.; Ando, S.; Nemoto, T.; Abe, Y.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease of unknown etiology that affects mostly young women. Multiorgan complications and prolonged treatment significantly cause physical and mental stress in patients. Improving patients' quality of life (QOL) in SLE treatment is essential. We examined the treatment effects on disease activity and QOL of SLE patients. Objectives: In recent years, lupus low disease activity state (LLDAS) has been proposed as a treatment target for SLE. Patients who achieve LLDAS have a low recurrence rate for lupus and a low risk of serious complications (1). The aim of this study is to investigate whether achieving LLDAS reduces not only recurrence rate and complications of SLE but also improves patients' QOL. Methods: A total of 104 SLE patients were enrolled in our prospective SLE registry study (Juntendo, Multi-center, Prospective cohort for investigation of clinical course and outcome in SLE: JUMP) conducted at our institution. SLE was diagnosed using the American College of Rheumatology (ACR) 1982 criteria (revised in 1997). QOL was evaluated using the standard version of the 36-item short form health survey version 2 (SF36v2). Participants were divided into the LLDAS achievement and non-achievement groups, and the characteristics of each group including results of SF36v2 were examined. Results: This study included 104 SLE patients, 94 female and 10 male, and the average age and disease duration were 46.4±13.8 and 14.5±11.3 years, respectively. The average corticosteroid dose was 8.0±17.4 mg/day in terms of prednisolone, and anti-dsDNA antibody titer was 16.8±38.5 IU/ml. Of the 104 patients, 57 achieved LLDAS. The subscale's standard scoring using SF36v2 for role physical (RP) was 78.9±24.0 and 64.6±27.6 (P<0.01), general health (GH) was 50.0±17.0 and 42.0±19.3 (P<0.05), vitality (VT) was 55.8±15.8 and 38.0±24.1 (P<0.01), social functioning (SF) was 82.0±20.7 and 66.5±26.3 (P<0.01), role emotional (RE) was 89.0±16.1 and 73.4±28.1 (P<0.01), and mental health (MH) was 72.4±15.9 and 58.3±21.8 (P<0.01) in the LLDAS achievement and non-achievement groups, respectively. Furthermore, scoring based on the national standard value in the LLDAS achievement group showed that two categories were >50. However, in the LLDAS non-achievement group, all categories were <50. In particular, RP, GH, VT, SF, RE, and MH of the LLDAS achievement group had significantly higher scores than the LLDAS non-achievement group (RP and GH: p<0.05 and VT, SF, RE and MH: p<0.01). Conclusion: Results of examining the association between LLDAS and QOL using SF36v2 in SLE patients showed that patients who achieved LLDAS had significantly better standard statistical scores in many subscale categories. Thus, LLDAS achievement as a treatment target for SLE patients greatly contributes to improving patients' QOL. References: [1]Franklyn K, et al. Definition and initial validation of a Lupus Low Disease Activity State (LLDAS).Ann Rheum Dis. 2016 Sep;75(9):1615-21. Disclosure of Interests: None declared